Who's Minding the Kids? Experimental Evidence on the Demand for Child Care Quality - James Gordon; Chris M. Herbst; Erdal Tekin (Institute of Labor Economics (IZA), 2018)
Despite the well-documented benefits of high-quality child care, many preschool-age children in the U.S. attend low-quality programs. Accordingly, improving the quality of child care is increasingly an explicit goal of government policy. However, accomplishing this goal requires a thorough understanding of the factors that influence parents' child care decisions. This paper provides the first credible evidence on the demand for child care characteristics in the market for home-based care. Using a randomized audit design, we study three dimensions of caregiving: affordability (i.e., the hourly price of child care), quality (i.e., caregiver education and experience), and convenience (i.e., caregiver car ownership and availability). We find that while parents are extremely sensitive to the cost of child care, they also have strong preferences for quality, particularly caregivers' educational attainment. Furthermore, we obtain mixed results on the convenience dimensions of child care, with parents valuing those owning a car but not those with more availability. Finally, we find significant heterogeneity in child care preferences according to families' age of youngest child, race and ethnicity, and willingness-to-pay. Our findings suggest that the child care market's quality problems may be driven by parents' inability to afford high-quality care or their lack of informational resources on how to identify such programs, rather than an unwillingness to pay for them.
Keywords: I21; I28; J01; J23; J24; 330; child care; early childhood; education; parent preferences; field experiments